Doing time online - Siebold, Jan. (Morton Grove, Ill. : Albert Whitman, 2002)
After he is involved in a prank that led to an elderly woman's injury, twelve-year-old Mitchell must make amends by participating in a police program in which he chats online with a nursing home resident.
Keywords: Old age; Nursing homes; Punishment